The use of platelet-rich plasma (PRP) to improve structural impairment of rat testis induced by busulfan. (19th May 2019) - Dehghani, Farzaneh; Sotoude, Narges; Bordbar, Hossein; Panjeshahin, M.R.; Karbalay-Doust, Saied
Abstract: Platelet-rich plasma (PRP) has a potential effect on tissue repair through proliferation and differentiation of tissue progenitor cells. The aim of this study was to evaluate the effect of PRP on the testis structure and function in infertile rat model by stereological method. Thirty-two male rats were divided into four groups. Infertility was induced by the administration of busulfan (BUS) (10mg/kg, I.P., single dose). PRP (80μl, testis local injected, single dose) was administered for the subjects. After 48 days, semen analysis was performed and blood samples were taken from the heart to measure the testosterone. Then, the left testis was removed, fixed, embedded, sectioned, and stained by H&E; after that the testes were analyzed. The results showed that BUS can decrease the sperm count, motility, normal morphology, length of the spermatozoon tail, volume of the testis, seminiferous tubules, germinal epithelium height, and the number of spermatogenesis lineage cells in comparison with the control group ( p < 0.01). PRP increased the number of spermatogenic stem cell, count, motility and tail length of the sperm and testosterone level in BUS-treated animal significantly, but it did not have any effect on the volume of the testis, germinal epithelium height, Sertoli and Leydig cells number, and seminiferous tubules length. It concluded that PRP can improve the structural and functional impairment of the testis in treatment by BUS.